2019
DOI: 10.1186/s12943-018-0930-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically upregulated oncoprotein PLCE1 drives esophageal carcinoma angiogenesis and proliferation via activating the PI-PLCε-NF-κB signaling pathway and VEGF-C/ Bcl-2 expression

Abstract: BackgroundEsophageal squamous cell carcinoma (ESCC) is one of the most lethal malignancies. Neovascularization during tumorigenesis supplies oxygen and nutrients to proliferative tumor cells, and serves as a conduit for migration. Targeting oncogenes involved in angiogenesis is needed to treat organ-confined and locally advanced ESCC. Although the phospholipase C epsilon-1 (PLCE1) gene was originally identified as a susceptibility gene for ESCC, how PLCE1 is involved in ESCC is unclear.MethodsMatrix-assisted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
366
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(373 citation statements)
references
References 52 publications
7
366
0
Order By: Relevance
“…In various human cancers, enhanced expression of VEGFC and higher levels of VEGFC in serum are commonly associated with tumor aggressiveness and lymph-node metastasis (Su et al, 2007;Lohela et al, 2009). In esophageal carcinoma, for instance, angiogenesis is driven via the phosphoinositide-phospholipase C-ε (PI-PLCε)/NF-κB signaling pathway by direct promotion of VEGFC transcription (Chen et al, 2019). In xenograft or transgenic tumor models, stimulation of lymphangiogenesis by VEGFC promotes malignant cell dissemination (Stacker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In various human cancers, enhanced expression of VEGFC and higher levels of VEGFC in serum are commonly associated with tumor aggressiveness and lymph-node metastasis (Su et al, 2007;Lohela et al, 2009). In esophageal carcinoma, for instance, angiogenesis is driven via the phosphoinositide-phospholipase C-ε (PI-PLCε)/NF-κB signaling pathway by direct promotion of VEGFC transcription (Chen et al, 2019). In xenograft or transgenic tumor models, stimulation of lymphangiogenesis by VEGFC promotes malignant cell dissemination (Stacker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sustained activation of NF-κB signaling pathway is a common event in various cancers, including PDAC, and considered to be essential to cancer development. Chen et al showed that PLCE1 constitutively activated the NF-κB signaling pathway to drive esophageal carcinoma angiogenesis and proliferation [41]. Jeong et al reported that miR-196b/Meis2/PPP3CC axis sustained the activation of NF-κB signaling pathway to induce prostate cancer castration resistance [42].…”
Section: Discussionmentioning
confidence: 99%
“…The high lethality rate of gliomas highlights the urgent need for e cient treatment. The pathogenesis of glioma is complex and can be induced by a variety of mechanisms, as shown by abnormal activation of glioma stem cells [28], tumor angiogenesis [29] and isocitrate dehydrogenase mutation [30]. VEGF acts as a regulator of angiogenesis has been widely recognized as a critical contributor to the development and progression of glioma [12,14].…”
Section: Discussionmentioning
confidence: 99%